IMPLEMENTATION OF RELIGIOUS CHARACTER EDUCATION IN STUDENTS THROUGH TAHFIDZ QUR'AN ACTIVITIES WITH TSAQIFA METHOD IN MUHAMMADIYAH VOCATIONAL HIGH SCHOOL 3 SURAKARTA - Alfaridzi, Muhammad Amir; Jafitri, Khabihiz; Purwanti, Oksita (Hunafa: Jurnal Studia Islamika, 2019)
This study aims are to describe (1) Application of tahsin and tahfidz activities with Tsaqifa method in learning the Qur’an at Muhammadiyah vocational high School 3 Surakarta. (2) Supporting and inhibiting factors of the application of the Tsaqifa method, and (3) Results in the activities of tahsin and tahfidz of the Qur’an using the Tsaqifa method. The research method used is descriptive qualitative. Sources of data in this study were teachers, students, and the learning process of the Qur’an subjects at Muhammadiyah vocational high School 3 Surakarta. The object of this study is the result of the teaching methods used by teachers in learning the Qur’an. Data collection uses interview, observation, and documentation techniques. The inhibiting factors are the large number of Qur’an reading skills still stammering, lack of interest in learning the Qur’an, and lack of infrastructure. Supporting factors namely internal factors are factors that arise from students themselves, and external factors namely family, institutional, and school environment. To overcome each problem or inhibiting factors are still being studied to find the right solution.